2015
DOI: 10.1002/rcs.1661
|View full text |Cite
|
Sign up to set email alerts
|

Video‐based 3D reconstruction, laparoscope localization and deformation recovery for abdominal minimally invasive surgery: a survey

Abstract: Video-based approaches have many advantages, such as providing intra-operative information without introducing extra hardware to the current surgical platform. However, an extensive discussion on this important topic is still lacking. This survey paper is therefore beneficial for researchers in this field. Copyright © 2015 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 161 publications
(255 reference statements)
0
37
0
Order By: Relevance
“…However, our findings indicated that laparoscopic surgery for ovarian cysts had less adverse effects than did laparotomy, and could better control the patient’s stress response and protect the patient’s ovarian reserve function. Many studies 25,26 have also reported the advantages of laparoscopic surgery for treating diseases. In a radial operation for carcinoma of the stomach, 27 use of laparoscopy results in less stress and immune responses to patients compared with traditional laparotomy.…”
Section: Discussionmentioning
confidence: 99%
“…However, our findings indicated that laparoscopic surgery for ovarian cysts had less adverse effects than did laparotomy, and could better control the patient’s stress response and protect the patient’s ovarian reserve function. Many studies 25,26 have also reported the advantages of laparoscopic surgery for treating diseases. In a radial operation for carcinoma of the stomach, 27 use of laparoscopy results in less stress and immune responses to patients compared with traditional laparotomy.…”
Section: Discussionmentioning
confidence: 99%
“…In 2002, Scharstein and Szeliski [27] introduced a taxonomy and evaluation of two-frame stereo dense matching algorithms, dividing it into four primary steps: Based on the implementation employed in the cost (support) aggregation step, dense matching can be divided into two categories: local algorithms and global algorithms. Local algorithms connect the matching costs within a local neighborhood and select the lowest matching cost as a disparity [30], that is "winner takes all 11 . Global algorithms typically define a global energy function which includes a data term and a smoothness term acting on the whole image instead of local cost aggregations [31].…”
Section: Two-frame Dense Matching In Photogrammetrymentioning
confidence: 99%
“…Applications of 3D information have extended from digital elevation model (DEM) and digital surface model (DSM) generation to many other fields including archeology [1,2], topographic monitoring [3,4], facial geometry and dynamic capture [5,6], cultural heritage protection [7,8], forest and agriculture modeling [9,10], and medical treatment [11]. Since laser scanning can produce highly accurate, reliable, dense, and more integrated 3D point clouds of objects [12], it has been utilized as the preferred technology for 3D modeling over the last two decades.…”
Section: Introductionmentioning
confidence: 99%
“…In gastroenterology, AI methods have been explored from both the classical model-driven and deep learning paradigms [20]. While the majority of work has focused on the detection or delineation of diseased regions [5,14,27], on the measurement of structural size [10] or the 3D navigation within the endoluminal organs [12,15,25], relatively little research effort has been invested into the classification of different endoscopic viewpoints that need to be viewed to complete an examination.…”
Section: Introductionmentioning
confidence: 99%